Abdominal Plain Radiograph in Neonatal Intestinal Obstruction - G Raghavendra Prasad; Amtul Aziz (EL-Med-Pub, 2016)
A comprehensive all-inclusive resource on plain radiograph in neonatal intestinal obstruction is presented. This is an attempt to develop a protocol and to regain expertise in evaluating a plain radiograph that most often yields more than enough clues to diagnose and to decide a plan of action.